The Impact of Stealth Marketing on Customer-based Brand Equity (CBBE): An Empirical Study on Electrical Industry Sector in Egypt - Ismail, Abdelrehim Nader Abdelrehim (The Arab Journal of Administration, 2024)
This study aimed to identify the concept of stealth marketing and its most important tools, to determine the impact of these tools on “The Customer-Based Brand Equity Applied” to the electrical appliance industry in Egypt. Stealth marketing is an independent variable represented in its tools (viral marketing - brand promoters - celebrity marketing) and its impact on the customer-based brand equity as dependent variable represented in its dimensions (brand awareness - brand Associations - brand Loyalty - perceived Quality). In order to achieve the objectives of the study, researcher adopted a questionnaire to collect primary data. The study sample included (270) individuals from general managers or their representatives in the companies under study. The study results showed that the most important of which is that stealth marketing affects the ability of companies operating in the electrical appliance industry in Egypt to create their Customer-Based Brand Equity, as it affects the brand image and increases customer loyalty to the brand.